Auranofin Mediates Mitochondrial Dysregulation and Inflammatory Cell Death in Human Retinal Pigment Epithelial Cells: Implications of Retinal Neurodegenerative Diseases - Yumnamcha, Thangal; Devi, Takhellembam Swornalata; Singh, Lalit Pukhrambam (Frontiers in Neuroscience, 2019)
Purpose Photoreceptor degeneration occurs in various retinal diseases including age-related macular degeneration (AMD), Retinitis pigmentosa (RP), and diabetic retinopathy (DR). However, molecular mechanisms are not fully understood yet. The retinal pigment epithelium (RPE) forms the outer blood retinal barrier (oBRB) and supplies glucose, oxygen and nutrients from the fenestrated choriocapillaris to photoreceptors for visual function. Therefore, RPE dysfunction leads to photoreceptor injury/death and progression of blinding eye diseases. This study aims to understand the role of the thioredoxin (Trx) and its reductase (TrxR) redox signaling in human RPE dysfunction and cell death mechanism(s) in an in vitro system. Methods A human RPE cell line (APRE-19) was cultured in DMEM/F12 medium and treated with auranofin (AF – 4 μM, an inhibitor of TrxR) for 4 and 24 h. Mitochondrial and lysosomal function, cellular oxidative stress and NLRP3 inflammasome activity were measured using cell assays, Western blotting, and confocal microscopy. Antioxidants and anti-inflammatory compounds were tested for blocking AF effects on RPE damage. Cell death mechanisms (LDH release to culture media) were determined using necroptosis, ferroptosis and pyroptosis inhibitors. P < 0.05 was considered significant in statistical analysis. Results Auranofin causes mitochondrial dysfunction (Δψm↓ and ATP↓), oxidative stress (H2O2↑) and mitophagic flux to lysosomes. Furthermore, the lysosomal enzyme (cathepsin L) activity is reduced while that of pro-inflammatory caspase-1 (NLRP3 inflammasome) is enhanced in ARPE-19. These effects of AF on ARPE-19 are inhibited by antioxidant N-acetylcysteine (5 mM, NAC) and significantly by a combination of SS31 (mitochondrial antioxidant) and anti-inflammatory drugs (amlexanox and tranilast). AF also causes cell death as measured by cytosolic LDH release/leakage, which is not inhibited by either ferrostatin-1 or necrostatin-1 (ferroptosis and necroptosis inhibitors, respectively). Conversely, AF-induced LDH release is significantly reduced by MCC950 and Ac-YVAD-cmk (NLRP3 and Caspase-1 inhibitors, respectively), suggesting a pro-inflammatory cell death by pyroptosis. Conclusion The Trx/TrxR redox system is critical for RPE function and viability. We previously showed that thioredoxin-interacting protein (TXNIP) is strongly induced in DR inhibiting the Trx/TrxR system and RPE dysfunction. Therefore, our results suggest that the TXNIP-Trx-TrxR redox pathway may participate in RPE dysfunction in DR and other retinal neurodegenerative diseases.